The United Nations Global Compact International Yearbook 2014 - United Nations Global Compact (United Nations, 2014)
The aim of the Global Compact International Yearbook is to create a global overview of the achievements of the UN Global Compact (UNGC). The book offers proactive and in-depth information on key sustainability issues to stakeholders around the world and promotes unique and comprehensive knowledge exchange and learning in the spirit of the Global Compact principles. Thus the publication helps to advance transparency, promotes the sharing of best-practices, and, perhaps most significantly, gives a strong voice to the regional and global actors that are at the heart of the initiative.